2019
DOI: 10.1021/acs.macromol.8b02351
|View full text |Cite
|
Sign up to set email alerts
|

From Polymerizable Ionic Liquids to Poly(ionic liquid)s: Structure-Dependent Thermal, Crystalline, Conductivity, and Solution Thermoresponsive Behaviors

Abstract: This contribution describes the synthesis of 3-alkyl-1-vinylimidazolium bromide ionic liquid monomers (ILMs), ion exchange with bis­(trifluoro­methane)­sulfonimide anion (NTf2 –), and their radical polymerization to a homologous series of poly­(ionic liquid)­s (PILs) containing an imidazolium ion substituted with alkyl chains of different lengths (C2(n=7–11)). Owing to the presence of a long alkyl chain, all the ILMs show crystalline phases whose melting point and melting enthalpy increase sharply with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 79 publications
1
26
0
Order By: Relevance
“…Ultimately, the decoupling of ion dynamics from segmental motion is the most promising approach to achieve high ionic conductivity in polymer electrolytes at room temperature. Moreover, there have been a series of studies to examine the effect of tuning of cation/anion size, 30,31 position of ions (either in the main chain or in the side chain) of PIL, 19,29,32,33 variation of molecular weight, 18 changing the space between neighboring PIL chains, 13 pressure exerted during conductivity measurement, 1 variation of chain length, 34 glass transition temperature ( T g ), 14,30,35 chain polarity, 36 etc., on the change of ionic transport in PIL systems. Dielectric spectroscopic (DS) technique is reported to be the most popular method to investigate ionic conductivity, ion transport and relaxation mechanism in electrolyte systems 29,37–39 .…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, the decoupling of ion dynamics from segmental motion is the most promising approach to achieve high ionic conductivity in polymer electrolytes at room temperature. Moreover, there have been a series of studies to examine the effect of tuning of cation/anion size, 30,31 position of ions (either in the main chain or in the side chain) of PIL, 19,29,32,33 variation of molecular weight, 18 changing the space between neighboring PIL chains, 13 pressure exerted during conductivity measurement, 1 variation of chain length, 34 glass transition temperature ( T g ), 14,30,35 chain polarity, 36 etc., on the change of ionic transport in PIL systems. Dielectric spectroscopic (DS) technique is reported to be the most popular method to investigate ionic conductivity, ion transport and relaxation mechanism in electrolyte systems 29,37–39 .…”
Section: Introductionmentioning
confidence: 99%
“…Polymers 2020, 12, 2159 2 of 14 PILs consist of repeating groups containing ionic pairs in the polymer chain [26][27][28]. They have the unique properties of ionic liquids and exhibit increased mechanical strength and durability [27,[29][30][31]. Ionic liquids (ILs) are mostly defined as green solvents, but nowadays the studies have indicated that some of them can be toxic [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Long alkyl side groups forming crystalline or LC mesophase are frequently introduced into imidazole-type ionic liquids (ILs), PILs, and PIL microgels. In this work, the PIL-containing BCPs with −C 22 H 45 long alkyl side groups, i.e., poly­(ethylene oxide)- b -poly­(1-((2-acryloyloxy)­ethyl)-3-docosylimidazolium) with X – as a counterion (PEO- b -P­(AOEDIm-X)), were synthesized. It was found that the breakout crystallization of −C 22 H 45 side groups led to the disordering of both the first- and second-level structures in the PEO- b -P­(AOEDIm-X) BCPs, which are formed by the microphase separation of PEO/PIL blocks and the long alkyl side groups/the other parts of the PIL block, respectively.…”
Section: Introductionmentioning
confidence: 99%